Simulação de fluxo de carga para sistemas de transmissão e distribuição com o ATPDraw - Ferreira, Pablo Fillype Teixeira (Universidade Federal Rural do Semi-Árido, 2021)
To solve the load flow problem, obtaining the state of operation of electrical power networks; is mathematically based, numerical methods of Gauss-Jacobi/Gauss-Seidel and Newton-Rapshon with variations of the decoupled and fast decoupled methods. Among the main tools that use these numerical methods are computational modeling programs. Even though such programs are great analysis tools, current demands need programs that are fast, and that simplify the modeling for transmission/distribution systems and operation of the power grid. The use of the ATPDraw Software is due to the simplification and practicality with the construction of its simulations based on the methods already established in the study of load flow, aligned with the graphical environment that facilitates the construction of the systems under analysis. ATPDraw is an excellent tool for such studies. The present work presents the modeling of a two-bus transmission system, with PQ and PV buses, the four-bus IEEE distribution system and example 24 of the ATP (IEEE 9 BUS Distance Protection). The simulations of the two-bus systems, the IEEE 4-bus system and the example 24 of ATPDraw made it possible to observe the electrical voltages in the system buses and the power flows in the transmission and distribution lines, thus proving the effectiveness of ATPDraw in the electrical network steady-state analysis
Keywords: Fluxo de Carga; Transmissão de Energia Elétrica; Distribuição de Energia Elétrica; Software ATPDraw; Load Flow; Electric Power Transmission; Distribution System; ATPDraw Software; ENGENHARIAS::ENGENHARIA ELETRICA